The effect of crumb rubber modification on the physical properties of porous asphalt / Mohd Rasdan Ibrahim - Mohd Rasdan , Ibrahim (2018)
Open graded friction course (OGFC) or porous asphalt (PA) system consists of a layer of porous asphalt, a layer of granular sub-base and a layer of crushed stone base course that acts as a reservoir. This allows water to infiltrate the surface course and stored at the base before the water reaches the subgrade. The popularity of this type of pavement is due to a number of advantages it have such as reduction in splash and spray, reduction of the risk of wet skidding and hydroplaning with lower noise generated from the traffic friction. In tropical counties such as Malaysia where the average monthly precipitation can be as high as 314mm, the use of open graded pavement system can be extremely beneficial. Due to its high porosity, porous asphalt can face problems such as faster oxidation rate of binder and loss of adhesion due to contact with water. Modified bitumen was utilised in the hope that it would further improve the performance of the porous asphalt. Crumb rubber modification by the wet process has been shown to have the ability to improve the rutting resistance, resilience modulus and fatigue cracking resistance of asphaltic mixes. This is due to the alteration to the property of the bituminous binder in terms of the viscosity, softening point, loss modulus and storage modulus. The outcome properties of crumb rubber modified bitumen (CRMB) is very sensitive and are highly governed by the mixing process which is dependent on external factors such as the mixing temperature, mixing duration and type; and internal factors such as type of bitumen, crumb rubber quantity, particle size, and type. This research studies the effect of particle size and crumb rubber content to the durability of an OGFC manufactured according to the Specifications for Porous Asphalt produced by the Road Engineering Association of Malaysia (REAM) modified with crumb rubber using the wet process. This study also conducted to determine the relations of rubber size, rubber content, and binder content in determination of optimum binder content (OBC) for OGFC with accordance to REAM specification. In order to analyse the performance of the binders and porous asphalt, a series of binder tests and bituminous mixtures tests were performed. In addition, multiple linear regression (stepwise method) was used for statistical analysis for which the main objective was to develop an equation (regression model) that could be used for predicting the performance of the mixtures for all factors engaged. A secondary purpose was to use regression analysis as a means of explaining the causal relationship among the factors (significant level). In the final analysis, the author found that rubber size, rubber content and binder content significantly affected the performance of porous asphalt. Moreover, this study showed that binder content between 6% and 6.5% is advisable to be used as the OBC to allow a certain level of tolerance when producing rubberized bitumen and at the same time ensuring a high quality product.